Visualization of fast "hydrogen pump" in core–shell nanostructured Mg@Pt through hydrogen-stabilized Mg3Pt. Issue 24 (3rd June 2019) - Lu, Chong; Ma, Yanling; Li, Fan; Zhu, Hong; Zeng, Xiaoqin; Ding, Wenjiang; Deng, Tao; Wu, Jianbo; Zou, Jianxin
Abstract : A core–shell nanostructured Mg@Pt composite, consisting many of icosahedral Mg particles as the core with nano-sized Pt particles distributed homogeneously on different surfaces, was synthesized through an arc plasma method followed by the generic solid-state method. Abstract : A core–shell nanostructured Mg@Pt composite, consisting many of icosahedral Mg particles as the core with nano-sized Pt particles distributed homogeneously on different surfaces, was synthesized through an arc plasma method followed by the generic solid-state method. The microstructures and hydrogen sorption properties of the Mg@Pt composite were carefully investigated and compared to that of pure Mg powder. In particular, the dehydrogenation behaviors of the hydrogenated Mg@Pt composite were observed in situ via high-resolution transmission electron microscopy (HRTEM). The results revealed that the Pt on Mg particles showed a "spillover" effect to improve the hydrogen absorption kinetics in the early stage. It then transformed into H-stabilized Mg3 Pt, followed by the formation of MgH2 . DFT calculation and in situ TEM observations demonstrated that the H-stabilized Mg3 Pt acted as a "hydrogen pump" for the dehydrogenation of MgH2 and then transformed into Pt after desorption. Through this effect, the dehydriding kinetics of the hydrogenated Mg@Pt composite was improved and the onset dehydrogenation temperature was reduced compared to that of the pure MgH2 powder.